Chapter Appendix VII: A Complete Table of Localizers - Huang, Chu-Ren (Taylor & Francis, 2017)
This monograph is a translation of two seminal works on corpus-based studies of Mandarin Chinese words and parts of speech. The original books were published as two pioneering technical reports by Chinese Knowledge and Information Processing group (CKIP) at Academia Sinica in 1993 and 1996, respectively. Since then, the standard and PoS tagset proposed in the CKIP report have become the de facto standard in Chinese corpora and computational linguistics, in particular in the context of traditional Chinese texts. This new translation represents and develops the principles and theories originating from these pioneering works. The results can be applied to numerous fields; Chinese syntax and semantics, lexicography, machine translation and other language engineering bound applications.